A case report showing unusual atrial communication with severe regurgitation of multiple valves and pulmonary aneurysm: double atrial septum with persistent interatrial space. Issue 7 (1st July 2021) - Ortiz de Murua, José Antonio; de la Fuente Blanco, Laura; Trigo-Bautista, Alberto; Ruiz-Olgado, María José
Abstract: Background: We discuss an unusual association: double atrial septum, pulmonary artery aneurysm, and severe regurgitation of multiple valves. Case summary: A 70-year-old man was admitted into the hospital because of progressive dyspnoea. Physical examination showed a blood pressure of 132/70 mmHg, a systolic murmur on the right upper sternal border, another systolic murmur at the apex, and a diastolic murmur at the lower left sternal border. Electrocardiogram revealed atrial fibrillation and complete left bundle branch block. Transthoracic echocardiography showed mitral prolapse, severe mitral, aortic, and pulmonary regurgitation, a 60 mm diameter pulmonary artery aneurysm, mild to moderate tricuspid regurgitation, and moderate pulmonary hypertension. Transoesophageal echocardiography also showed an unusual atrial communication consisting of a double atrial septum with a mid-line chamber between both atria. A cardiac magnetic resonance scan was performed and confirmed echocardiography findings and QP :QS ratio = 1.3. Discussion: In our knowledge, this is the first case report with this association. We present the main clinical features of the double atrial septum with persistent interatrial space, its echocardiography anatomy, differential diagnosis, and embryology.